1989
DOI: 10.1017/s0950268800030740
|View full text |Cite
|
Sign up to set email alerts
|

Intradermal hepatitis B immunization with yeast-derived vaccine: serological response by sex and age

Abstract: SUMMARYThe efficacy and acceptability of yeast-derived recombinant hepatitis B vaccine given by the intradermal route was investigated in 221 healthl care volunteers. Two hundred and sixteen received a full course of three doses of vaccine. Only one subject was withdrawn because of a significant adverse reaction (psoriasis). The vaccine stimulated an antibody response in 81 %. The response to the vaccine was better in women than in men (87 % compared with 71 %, p = 0 007) and in women below the age of 40 years… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0
1

Year Published

1990
1990
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(13 citation statements)
references
References 18 publications
1
11
0
1
Order By: Relevance
“…Many authors have used the intradermal route with variable responses [21][22][23][24], Gonzales et al [25] compared the intradermal and intramuscular routes of hepatitis B vacci nation. They noted a 78.1% seroconversion rate in a three-dose schedule (0, 1 and 6 months), while Morris et al [26] obtained a slightly higher seroconversion rate.…”
Section: Discussionmentioning
confidence: 95%
“…Many authors have used the intradermal route with variable responses [21][22][23][24], Gonzales et al [25] compared the intradermal and intramuscular routes of hepatitis B vacci nation. They noted a 78.1% seroconversion rate in a three-dose schedule (0, 1 and 6 months), while Morris et al [26] obtained a slightly higher seroconversion rate.…”
Section: Discussionmentioning
confidence: 95%
“…The conclusions of this meta‐analysis appear to confirm the results of HBV vaccination in patients with normal renal function. The relationship between age and response to hepatitis B vaccine in the general population had been addressed by several authors with conflicting results; 10, 11 however, a recent review 12 noted a consistent association between older age and risk of non‐response to HB vaccine. This finding is biologically plausible, as numerous changes in cellular and humoral immune responses have been described in older individuals 8, 9 …”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that age‐associated changes in humoral and cellular immune function may decrease vaccine effectiveness in older individuals, compared with children or young adults 8, 9 . However, recent research related to this topic has yielded contradictory findings in the general population 10–12 . This issue is of practical importance, as the different efficacy of the vaccine in different age groups could change the optimal vaccination policy.…”
Section: Introductionmentioning
confidence: 99%
“…A previous meta-analysis in 2002 observed many factors influencing response to hepatitis B vaccine, especially a decrease response to recombinant HBV vaccine at higher ages11, which suggested that earlier vaccination should be prioritized for prevention at the population level. However, in the last decade, numerous emerging reports, which focused on the seroprotection rate of hepatitis B vaccine in adults12131415161718192021222324252627282930313233343536373839404142434445464748, are still inconclusive to immunize what adults are the most appropriate in order to increase the seroprotection rate. Factors influencing immunologic response to hepatitis B vaccine in adults have been inconsistently examined in existing studies.…”
mentioning
confidence: 99%